PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IV SD - Oktavia, Linda; Hajani, Tri Juli; Egok, Asep Sukenda (Unversitas Katolik Santo Thomas, 2022)
This research aimed to find out the science learning outcomes of fourth grade students of SD Negeri 1 Remban after applying the Contextual Teaching And Learning (CTL) model. The method experimental with the form pre-test post-test design. Population and sampel or research subject all Fourth graders of SD Negeri 1 Remban for the academic year 2021/2022 for grade IV totaling 15 Students. Data Collection techniques with a total of 8 questions. Data Analysis techniques using the Z-test. The results showed based on the results of the Z-test with a significant level of 5%, obtained Z-hitung >Z-tabel (7,43 > 1,64) which shows that the hypothesis Ho is rejected and Ha is accepted. Conclusion that the fourth grade science learning outcomes of SD Negeri 1 Remban after the application of the Contextual Teaching And Learning (CTL) were significantly completed. The average value of the final science study test was 81.